Conceptualizing the Multicultural ‘North’ in the Íslendingasögur: Peoples, Places, and Phenomena - Wang, Solveig Marie (Nordlit, 2020)
Despite often being described as ‘desolate’ and ‘remote’ (especially in the terra nullis colonialism exercised by the Scandinavian nation states in early modern times), the northernmost parts of the Fennoscandian landscape complexes are described as already inhabited in several medieval Scandinavian texts, including the Íslendingasögur. Primarily, these texts explicitly assert that the ambiguous and distant ‘north’ of Fennoscandia was a special, preternatural place, simultaneously internal and external to what medieval Icelanders perceived as ‘Nóregi’. Whether enforced by the ‘othering’ of characters depicted with expressive features and abilities traditionally associated with the area or its indigenous inhabitants, by the descriptions of different landscapes and communities unequivocally ‘othered’ and distinct from that of the saga-writers’ reality, or by extraordinary phenomena connected to the two, ‘norðarliga í Nóregi’ is portrayed as somewhat distinct from that of the rest of the ‘national’ landscape. Encompassing an area extending further south than contemporary northern Norway, the notion of a supernatural north in the Íslendingasögur goes beyond an idea of a unified Nóregi. By discussing the portrayal of north Norwegian landscapes and geographical understandings in these texts, in conjunction with an examination of the depiction of the Sámi, this essay aims to demonstrate how north Norwegian spatial awareness in the Íslendingasögur can help enlighten cross-cultural relationships and liminal identities, and present fewer rigid contrasts between people and cultures in Fennoscandia than previously accounted for.